Physical Rehabilitation Outcomes in Patients with Dementia Following Hip Fracture Surgery: A Review - Wantonoro, Wantonoro; Dewi, Suarse; Suryaningsih, Endang Koni; Suprayitno, Edy (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Dementia patients were reported of having high risk for hip fracture. Rehabilitation programs were still being debated for this vulnerable population and the recovery outcomes in this frail elderly population are varied, thus evidenced-based outcomes for this issue are needed.Objective: To investigate rehabilitation programs, especially on physical function outcomes in patients with dementia following hip fracture surgery.Method: PubMed, Scopus and MEDLINE (EBSCO) databases were searched from January 2000 to June 2020 concerning rehabilitation intervention program in dementia patients who received hip surgical treatment. The studies included have the following criteria, (1) investigating physical outcomes of rehabilitation programs (2) Randomized controlled trials (RCTs) study design, (3) study involving dementia patients following hip fracture surgery (4) English full-text journal.Results: Six studies were included in this review. Most study focused on interdisciplinary or multidisciplinary rehabilitation program. Physical outcomes of rehabilitation programs seem to improve physical function, maintaining physical ability for ambulation, and decrease the risk of falls in mild or moderate dementia patients following hip fracture surgery. However, the physical function of older persons with dementia confirmed to be lower than those without dementia.Conclusion: Rehabilitation may show benefit for physical function in elderlywith mild or moderate dementia following hip fracture surgery, and this population needs to be included in the clinical rehabilitation program. Investigating and establishing the strategies to improve outcomes for dementia population is needed for future study.Â